To Use or Not to Use Opioid Analgesia for Acute Abdominal Pain Before Definitive Surgical Diagnosis? A Systematic Review and Network Meta-Analysis - Gavriilidis, Paschalis (J Clin Med Res, 2019)
BACKGROUND: Despite the existing evidence, many physicians are reluctant to use opioid analgesia for acute abdominal pain. METHODS: We performed updated conventional and network meta-analyses. For the first time to our knowledge, direct and indirect evidence of any type of opioid analgesia was estimated and compared using network meta-analysis. RESULTS: There was no significant difference in the intensity of pain between the two cohorts (mean difference (MD) = 0.43 (-0.05 to 0.91), P = 0.08). In addition, no significant difference was detected in the rate of incorrect diagnoses between the opioid analgesia and the placebo cohorts (odds ratio (OR) = 0.79 (0.54 to 1.17), P = 0.24). Network meta-analysis demonstrated that the results of direct evidence of head-to-head comparisons of opioid analgesics with placebo were in accordance with the results of conventional meta-analysis. Moreover, estimation and comparison of the indirect evidence on the four opioid analgesics did not demonstrate significant differences in effect size. CONCLUSIONS: Any type of opioid analgesic can be used safely for acute abdominal pain without risk of impairment of diagnostic accuracy.